Rare Association between Congenital Dorsal Dermal Sinus with Tethered Cord Syndrome: A Case Report - Sonia, Sheikh Farjana; Zaman, Mashaya; Mahmood, Ehsan; Hassan, Mohammad Sayeed; Banu, Selina Husna (Journal of National Institute of Neurosciences Bangladesh, 2024)
Congenital dermal sinus tract is an innocent‑appearing spinal dysraphism that may lead to devastating morbidities if not timely addressed. Congenital dermal sinus may be associated tethered cord syndrome. Here we report one patient who is presented at the age of eighteen months with lower limb weakness at Dr. M R Khan Shishu Hospital and ICH and was diagnosed as dorsal dermal sinus with teathered cord syndrome. Our aim is to illustrate the advantages of the early diagnosis of this rare treatable disorder and to prevent neurological sequelae. Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):151-156